Peminatan Motion Graphic Sebagai Konten Promosi Bisnis Start-Up Pada Media Sosial - Hong, Florencia Siswanto (Jurnal Vicidi, 2019)
The increasingly massive use of social media in Indonesia is both an opportunity and a challenge for start-up business owners when they are going to market their business. This research aims to determine how attracted start-up business owners in Indonesia towards the application of motion graphic as promotional content used in social media. Research methods that conducted in this research are qualitative research method by interviewing expert and extreme users, also doing literature study, and as well as quantitative research method by distributing online questionnaire to social media users and start-up business owners. From the results gathered, it can be concluded that motion graphic is an attractive content, so start-up business owners are interested and start thinking to use motion graphic as promotional content for their social medias.